2014
DOI: 10.1089/ars.2012.5129
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase 1, a Novel Molecular Source of ROS in Hippocampal Neuronal Death in Vascular Dementia

Abstract: Aims: Chronic cerebral hypoperfusion (CCH) is a common pathological factor that contributes to neurodegenerative diseases such as vascular dementia (VaD). Although oxidative stress has been strongly implicated in the pathogenesis of VaD, the molecular mechanism underlying the selective vulnerability of hippocampal neurons to oxidative damage remains unknown. We assessed whether the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (Nox) complex, a specialized superoxide generation system, plays a rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 78 publications
2
52
0
Order By: Relevance
“…Another study showed that NOX1 and NOX3 mRNA levels are increased in the brain during early stages of AD [201]. Interestingly, NOX1 mRNA levels were also reported to be significantly elevated in the hippocampal CA1 region in a bilateral cerebral artery occlusion (BCCAO) rodent model of vascular dementia, and the effect correlated with increased superoxide and ROS levels [202]. As a whole, these studies provide correlational evidence of increased NADPH oxidase subunit expression and NADPH oxidase activity in the brain in AD, which could contribute to AD pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that NOX1 and NOX3 mRNA levels are increased in the brain during early stages of AD [201]. Interestingly, NOX1 mRNA levels were also reported to be significantly elevated in the hippocampal CA1 region in a bilateral cerebral artery occlusion (BCCAO) rodent model of vascular dementia, and the effect correlated with increased superoxide and ROS levels [202]. As a whole, these studies provide correlational evidence of increased NADPH oxidase subunit expression and NADPH oxidase activity in the brain in AD, which could contribute to AD pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Overproduction of reactive species oxygen (ROS) and inflammation resulting from ischemia are two major contributors to the pathogenesis of VD . During CCH, endogenous antioxidants decrease, along with an increase in oxidative damage to protein, lipid, and DNA .…”
Section: Introductionmentioning
confidence: 99%
“…4 Overproduction of reactive species oxygen (ROS) and inflammation resulting from ischemia are two major contributors to the pathogenesis of VD. 5,6 During CCH, endogenous antioxidants decrease, along with an increase in oxidative damage to protein, lipid, and DNA. 7 As an intracellular endogenous regulator of oxidative stress and inflammation, thioredoxin-interacting protein (TXNIP) played a critical part in ischemic diseases in many studies.…”
Section: Introductionmentioning
confidence: 99%
“…11 12 Indeed, previous studies have shown that superoxide production by NADPH oxidase underlies cognitive impairment after cerebral ischaemia and traumatic brain injury. [13][14][15] However, the role of NADPH oxidase in memory impairment has not been examined in animals exposed to anaesthesia in the neonatal period. Furthermore, it is not known whether targeting NADPH oxidase during anaesthesia protects the neonatal brain from long-term memory deficits.…”
mentioning
confidence: 99%